Atlas : How to Carry the World on One's Back? - Didi - Huberman, Georges; Museo Nacional Centro de Arte Reina Sofia, Madrid; ZKM, Zentrum für Kunst und Medientechnologie, Karlsruhe; Sammlung Falckenberg, Hamburgo (Madrid : MNCARS - Museo Nacional Centro de Arte Reina Sofia, 2011)
Abad, Francesc ; Aballi, Ignasi ; Akhunov, Vyacheslav ; Albers, Josef ; Alighiero e Boetti ; Aragon, Louis ; Breton, André ; Arp, Hans ; El Lissitzky ; Baldessari, John ; et al.
Museo Nacional Centro de Arte Reina Sofia, Madrid, November 6, 2010 - March 28, 2011 / ZKM Museum für Neue Kunst, Karlsruhe, May 7 - August 28, 2010 / Sammlung Falckenberg, Hamburgo, September 24 - November 27, 2011
kunstcatalogus